2022
DOI: 10.3390/genes13071264
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic, Respirational, and Growth Responses of Six Benthic Diatoms from the Antarctic Peninsula as Functions of Salinity and Temperature Variations

Abstract: Temperature and salinity are some of the most influential abiotic parameters shaping biota in aquatic ecosystems. In recent decades, climate change has had a crucial impact on both factors—especially around the Antarctic Peninsula—with increasing air and water temperature leading to glacial melting and the accompanying freshwater increase in coastal areas. Antarctic soft and hard bottoms are typically inhabited by microphytobenthic communities, which are often dominated by benthic diatoms. Their physiology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 92 publications
(140 reference statements)
2
7
0
Order By: Relevance
“…All measured P–I curves exhibited a typical shape without photoinhibition, as already reported for some of the species in detail in Prelle et al ( 2022 ). The key parameters NPP max and respiration were selected for all species before and after dark incubation ( Table 2 ), and species-specific responses could be outlined.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…All measured P–I curves exhibited a typical shape without photoinhibition, as already reported for some of the species in detail in Prelle et al ( 2022 ). The key parameters NPP max and respiration were selected for all species before and after dark incubation ( Table 2 ), and species-specific responses could be outlined.…”
Section: Resultssupporting
confidence: 85%
“…D300_015 was only identified at the genus level as Planothidium sp. in Prelle et al ( 2022 ). Morphological and molecular investigations showed that strain D300_025 is the same species.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Our sample location at 15 m water depth from a sediment biofilm in a marine environment is quite different from the type locality. Prelle et al (2022) verified a broad salinity tolerance for this species, supporting its presence and adaptation to different habitats. Growth of this species in culture was proven at 0-65 S A (absolute salinity) and a photosynthetic potential up to 100 S A .…”
Section: Monophyly Of the Genus Chamaepinnulariasupporting
confidence: 58%
“…Algal respiration rates in darkness are known to vary by two orders of magnitude (Geider & Osborne, 1989). A study of six Antarctic benthic diatoms showed 5‐fold variability in respiration rates between species as well as temperature dependence of respiration rates (Prelle et al, 2022). Therefore, differences in respiration rates and the capacity to store energy reserves may to a large extent explain how long species can maintain photosynthetic fitness in darkness.…”
Section: Discussionmentioning
confidence: 99%